Different but stable - gender-specific competitive behavior across age - Anna Katharina Pikos; Alexander Straub (Leibniz Universität Hannover, Wirtschaftswissenschaftliche Fakultät, 2021)
There is mixed evidence for gender differences in competing against the opposite sex. We analyze performance data from a sport where men and women can compete directly against each other. Our unique data consists of close to 600,000 observations from around 23,500 mixed-gender ninepin bowling games in Austria and the Czech Republic. To account for possible self-selection into competition against the opposite gender, we use the opponent team's sex composition as an instrument. We and almost no gender differences in Austria. In Czechia, men perform better against women and women worse against men. This pattern is stable across age.
Keywords: J16; D90; Z22; 330; gender; gender gap in competition; sports economics